1997
DOI: 10.1177/008124639702700404
|View full text |Cite
|
Sign up to set email alerts
|

Intragroup Accounts of Teenage Motherhood: A Community Based Psychological Perspective

Abstract: Using community based and women-centred perspectives, this study explored experiences of unplanned motherhood during adolescence. Ten African teenage mothers from a semi-rural area in KwaZulu-Natal volunteered to meet once a week for eight weeks to discuss their experiences of pregnancy and motherhood. The findings are discussed in the context of the effect of teenage motherhood on self, on family and peer relationships, traditional Zulu customs, and community support. Current relationships with partners and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…This is illustrated by the following: There was thus a perception of moral sanctions against both extramarital pregnancies and abortion. These findings link with those of other studies that showed negative reactions by parents and community members towards teenage pregnancies (De Visser & Le Roux, 1996;Parekh & De la Rey, 1997;Thobejane, 2001). …”
Section: People Will Come and Ask Me How Could I Do Something Like Thsupporting
confidence: 91%
“…This is illustrated by the following: There was thus a perception of moral sanctions against both extramarital pregnancies and abortion. These findings link with those of other studies that showed negative reactions by parents and community members towards teenage pregnancies (De Visser & Le Roux, 1996;Parekh & De la Rey, 1997;Thobejane, 2001). …”
Section: People Will Come and Ask Me How Could I Do Something Like Thsupporting
confidence: 91%
“…Female participants also felt unsupported in the sense that their relationships with the fathers of their children were often disapproved of, and family members frequently tried to keep them from what Kershaw et al, (2013:299) view as a potentially significant source of support. Some South African studies have indicated that adolescent mothers need more emotional support from parents and sorely miss peer and partner support (De Visser & Le Roux, 1996;Parekh & De la Rey, 1997). Adolescent fathers, in turn, have expressed a need for increased support in the practical and informational spheres (Swartz & Bhana, 2009:94,96).…”
Section: Discussionmentioning
confidence: 99%
“…Fox and Inazu (1980) reported similar findings, namely that few parents gave much direct instruction about sexuality, sexual intercourse or contraception. Respondents had mainly discussed sex with their peers or had learnt about it from the media, both of which were unreliable and sensationalised sex and promiscuity (Parekh & De la Rey, 1997). The authors endorse the view of Mayekiso and Twaise (1992), who believe that parents should be key informants about sex, a difficulty in traditional homes as sex is not openly discussed (Wilbraham, 2002).…”
Section: Communication About Sexmentioning
confidence: 99%